Identification of Potential Peptide Marker(s) for Evaluating Pork Meat Freshness via Mass Spectrometry-Based Peptidomics during Storage under Different Temperatures - Zhenqian Wei (Foods, 2022)
This study applied peptidomics to investigate potential biomarkers for evaluating pork-meat freshness. The spoilage time points of pork meat stored at −2, 4, 10, and 25 °C were defined by evaluating meat freshness indicators (color, total viable count, pH, and total volatile basic nitrogen). Peptide MVHMASKE was identified as a potential peptide marker via multivariate analysis. Pearson correlation revealed a negative correlation between intensity of MVHMASKE and total viable count/total volatile basic nitrogen. In addition, the correlation between peptide content and the change in pork-meat freshness was verified using real-life samples, and the content of MVHMASKE showed a significant decline during storage under 4 and 25 °C, correspondingly reflecting the change of pork meat from fresh to spoiled. This study provides favorable evidence to evaluate pork-meat freshness by monitoring the change of peptide MVHMASKE in content based on mass spectrometry-based peptidomics.